Antiparasitic activity of Astragalus brachycalyx subsp. brachycalyx extract against hydatid cyst protoscoleces and its effect on induction of apoptosis: an in vitro and ex vivo study - Javad Ghasemian Yadegari; Amal Khudair Khalaf; Massumeh Saadatmand; Hossein Mahmoudvand (Shahrekord University of Medical Sciences, 2022)
Introduction: This study aims to evaluate in vitro and ex vivo antiparasitic activity of Astragalus brachycalyx subsp. brachycalyx. root chloroformic extract against hydatid cyst protoscoleces and its effect on induction of apoptosis. Methods: Various concentrations of the A. brachycalyx root chloroformic extract (56.25, 112.5, 225, and 450 mg/mL) were treated with hydatid cyst protoscoleces collected from the liver of infected sheep for 5-60minutes in vitro and ex vivo. Eosin exclusion test was also utilized to measure the mortality of protoscoleces. Moreover, the extract effect was assessed on apoptosis induction in hydatid cyst protoscoleces by caspase-3 activity measurement. Results: The mortality rate of protoscoleces in in vitro was 100% after being exposed to 450 and 225 mg/mL of A. brachycalyx extract for 20 and 30 minutes and in ex vivo for 30 and 60 minutes, respectively. Following 48 h treatment of protoscoleces, A. brachycalyx chloroformic extract at the doses of 56.25, 112.5, 225, and 450 mg/mL, dose-dependently motivated the caspase-3 enzyme ranging from 8.8% to 29.6% Conclusion: A. brachycalyx root chloroformic extract had a significant protoscolicidal effect; however, extra surveys are required to assess its efficacy and safety as a promising protoscolicidal agent in clinical settings.